Telehealth for India: Looking beyond the Covid-19 pandemic - Babu, Ajit N. (ASCI: Journal of Management)
Telemedicine has been a buzzword in India since the 1990s. In 2020, due to the COVID-19 pandemic in India, a national lockdown limited access to in-person healthcare services. The Ministry of Health & Family Welfare issued India$1 (Bs first set of government guidelines for the use of telemedicine. Emphasis was placed on training doctors and gearing up teleconsultations. This effort led to a significant increase in consultations and the recruitment of additional clinicians to practice telemedicine. However, there remain challenges relating to privacy, patient data storage, unevenness in telecom infrastructure and a systematic approach to integrating teleconsultation data with the overall patient record and public health information systems. This paper will provide an overview of telehealth, examine key interventions that have occurred in India during the pandemic and explore potential future approaches that can leverage the benefits of telehealth across the health care spectrum.- Reproduced s